Karakteristik dan Diagenesis beberapa Percontoh Batuan Oil Shale Formasi Kasiro Terpilih, di Jambi dan Sumatera Selatan berdasarkan Scanning Electron Microscope (SEM) - Mohammad Heri Hermiyanto; Hermes Panggabean (Jurnal Geologi dan Sumberdaya Mineral, 2006)
Oil shale, as one of alternative energy resources, is recognized in the Late Eosen - Oligocene Kasiro Formation, located in the Rawas Ulu and Batang Asai areas. Based on SEM analysis, the shale  consists of smektite-illite, illite,  kaolinite, organic matter as liptinite (sporinite,and alginite) and contains oil droplet.The oil shale is composed of smectite-illite and illite characterised by wavy parallel fissile,while kaolinite clays show irregular shape characters. The shale has undergone a diagenetic process within an early mesodiagenetic level. Organic matter maturity level of the oil shale, in general, is the immature up to early mature. Keywords : oil shale,clay minerals,smectite-illite,  organic matter